The impact of HIPEC vs. EPIC for the treatment of mucinous appendiceal carcinoma: a study from the US HIPEC collaborative. (1st January 2020) - Leiting, Jennifer L.; Day, Courtney N.; Harmsen, William S.; Cloyd, Jordan M.; Abdel-Misih, Sherif; Fournier, Keith; Lee, Andrew J.; Dineen, Sean; Dessureault, Sophie; Veerapongh, Jula; Baumgartner, Joel M.; Clarke, Callisia; et al.
Abstract: Introduction: Mucinous appendiceal carcinoma is a rare malignancy that commonly spreads to the peritoneum leading to peritoneal metastases. Complete cytoreduction with perioperative intraperitoneal chemotherapy (PIC) is the mainstay of treatment, administered as either hyperthermic intra peritoneal chemotherapy (HIPEC) or early post-operative intraperitoneal chemotherapy (EPIC). Our goal was to assess the perioperative and long term survival outcomes associated with these two PIC methods. Materials and methods: Patients with mucinous appendiceal carcinoma were identified in the US HIPEC Collaborative database from 12 academic institutions. Patient demographics, clinical characteristics, and survival outcomes were compared among patients who underwent HIPEC vs. EPIC with inverse probability weighting (IPW) used for adjustment. Results: Among 921 patients with mucinous appendiceal carcinoma, 9% underwent EPIC while 91% underwent HIPEC. There was no difference in Grade III–V complications between the two groups (18.5% for HIPEC vs. 15.0% for EPIC, p =.43) though patients who underwent HIPEC had higher rates of readmissions (21.2% vs. 8.8%, p <.01). Additionally, PIC method was not an independent predictor for overall survival (OS) or recurrence-free survival (RFS) after adjustment on multivariable analysis. Conclusions: Among patients with mucinous appendiceal carcinoma, both EPIC and HIPEC appear to be associated with similar perioperative and long-term outcomes.